An Analysis of Students’ Ability In Writing Descriptive Text at The Tenth Grade Students of SMAN 11 Jambi Academic Year 2017/2018 - Prasetyo Hariyadi, Wennyta, Nurul Fitri (Universitas Batanghari Jambi, 2018)
Abstract The purpose of this research is to analyze the student’s ability in writing descriptive text at the tenth grade student of SMAN 11 Jambi academic year 2017/2018. This research used descriptive research with qualitative method. This research used Random Sampling to get the sample and then got X MIPA 3 as a sample with the total 35 students but two students did not follow the test. There were 33 students as a sample. In collecting data, the instrument of this research is writing test by using descriptive text. The findings of this research showed that, the student’s ability in writing descriptive text was categorized 18 students or (55%) were categorized as good, 9 students (27%) were categorized as excellent, 5 students (15%) were categorized as satisfactory, 1 student (3%) were categorized as unsatisfactory and there were no student who categorized failed. The researcher concluded that the student’s ability in writing descriptive text at the tenth grade student of SMAN 11 Jambi is Good because from 33 students 18 students or (55%) got score 13 – 16 and the level of student’s ability is good.Keywords: Writing Skill, Descriptive Text